Analisa Pengaruh Penampang Penghantar Terhadap Rugi Rugi Daya Korona Pada Sutet 275 kV - Saraswati, Eka Marta (Journal on Pustaka Cendekia Informatika, 2023)
This calculation aims to obtain the value of power losses caused by the condition of the conductor wire. The research results show that the corona power loss value is affected by the vd value due to good or bad weather, so if the weather is good then the corona power loss value will be low, whereas if the vd value is bad weather then the corona power loss value increases. Where the m0 value used of 0.83 can produce a critical voltage value of 144.77 kV/cm, the m0 value used of 0.84 can produce a critical voltage value of 146.52 kV/cm, the m0 value used of 0.85 can produce a voltage value the critical voltage is 148.27 kV/cm, the m0 value used is 0.86, the critical voltage value is 150.02 kV/cm, the m0 value used is 0.87, the critical voltage value is 151.77. So it can be concluded from the calculation above that if If the m0 value is increased, the resulting vd value will increase, and if the m0 value is decreased, the vd value will decrease.